Long Non-coding RNA TUG1 Sponges Mir-145a-5p to Regulate Microglial Polarization After Oxygen-Glucose Deprivation - Wang, Haoyue; Liao, Songjie; Li, Hongjie; Chen, Yicong; Yu, Jian (Frontiers in Molecular Neuroscience, 2019)
Microglia plays a critical role in neuroinflammation after ischemic stroke by releasing diverse inflammatory cytokines. Long non-coding RNA taurine up-regulated gene 1 (lncRNA TUG1) is widely expressed in adult brain and has been reported to participate in multiple biological processes associated with nervous system diseases. However, the role of TUG1 in microglial activation remains unidentified. BV-2 microglial cells were cultured in vitro and TUG1 siRNA was used to knock down its RNA level. Microglial cells were subjected to oxygen-glucose deprivation (OGD) for 4 hours following TUG1 siRNA or scramble siRNA transient transfection. After 24 hours reoxygenation, TUG1 level and microglial M1/M2 phenotype, as well as releasing inflammatory cytokines and their role to viability of SH-SY5Y neuroblastoma cells were determined by quantitative real-time PCR, ELISA, immunofluorescence and western blot. In addition, miR-145a-5p, a putative microRNA to bind with TUG1 by bioinformatics analysis, was simultaneously examined, then the interaction of TUG1 with miR-145a-5p and the potential involvement of NF-κB pathway were further evaluated by RNA-RNA pull-down assay and western blot. The cellular level of TUG1 was transiently up-regulated in microglial cells 24 hours after OGD treatment, with an inverse correlation to downregulated miR-145a-5p. TUG1 knockdown drove microglial M1-like to M2-like phenotypic transformation with reduced production of pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-6) and incremental release of anti-inflammatory cytokine (interleukin-10), as a result, promoted the survival of SH-SY5Y cells. Meanwhile, TUG1 knockdown prevented OGD-induced activation of NF-κB pathway as well, represented by decreased ratios of p-p65/p65 and p-IκBα/IκBα proteins. Furthermore, we found that TUG1 could physically bind to miR-145a-5p while miR-145a-5p inhibitor abolished the protective effects of TUG1 knockdown through activation of NF-κB pathway, suggesting a negative interaction between TUG1 and miR-145a-5p. Our study demonstrated that lncRNA TUG1, sponging miR-145a-5p with negative interaction, could regulate microglial polarization and production of inflammatory cytokines at a relatively early stage after OGD insult, where NF-κB pathway might be involved, possibly providing a promising therapeutic target against inflammatory injury.